Fields of learning : the student farm movement in North America - Sayre, Laura Browne, 1970-; Clark, Sean. (Lexington, Ky. : University Press of Kentucky, 2011)
Where will the next generation of farmers come from? What will their farms look like? Fields of Learning: The Student Farm Movement in North America provides a concrete set of answers to these urgent questions, describing how, at a wide range of colleges and universities across the United States and Canada, students, faculty, and staff have joined together to establish on-campus farms as outdoor laboratories for agricultural and cultural education. From one-acre gardens to five-hundred-acre crop and livestock farms, student farms foster hands-on food-system literacy in a world where the shortc.
Roots. Berea College (1871) : the work college legacy / Sean Clark -- Wilmington College (1946) : balancing education and profitability / Monte R. Anderson and Roy Joe Stuckey -- Sterling College (1962) : working hands, working minds / Julia Shipley -- Back to the land. Evergreen State College (1972) : interdisciplinary studies in sustainable agriculture / Stephen Bramwell, Martha Rosemeyer, and Melissa Barker -- University of Oregon (1976) : designing for change / Ann Bettman -- University of California, Davis (1977) : moving from the margins toward the center / Mark Van Horn -- Hampshire College (1978) : the agricultural liberal arts / Lorna Coppinger and Ray Coppinger -- Coming of age. University of Maine (1994) : majoring in sustainable ag / Marianne Sarrantonio -- Central Carolina Community College (1995) : growing new farmers / Robin Kohanowich -- Prescott College (1996) : agroecology as the cultivation of soil and mind / Tim Crews -- University of Montana (1997) : agriculturally supported community / Josh Slotnick -- New directions. University of British Columbia (2000) : the improbable farm in the world city / Mark Bomford -- New Mexico State University (2002) : planting an OASIS / Constance L. Falk and Pauline Pao -- Michigan State University (2003) : four-season student farming / John Biernbaum -- Yale University (2003) : a well-rounded education / Melina Shannon-DiPietro -- Conclusion: Starting a student farm / Laura Sayre and Sean Clark -- Appendix: An inventory of student farm projects in the United States and Canada.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: School farms -- United States; Agricultural students -- United States; Agricultural education -- United States; Agricultural colleges -- United States; Agriculture -- Fieldwork -- United States; School farms -- Canada; Agricultural students -- Canada; Agricultural education -- Canada; Agricultural colleges -- Canada; Agriculture -- Fieldwork -- Canada; Écoles pratiques d'agriculture -- États-Unis.; Étudiants en agriculture -- États-Unis.; Enseignement agricole -- États-Unis.; Écoles d'agriculture -- États-Unis.; Agriculture -- Recherche sur le terrain -- États-Unis.; Écoles pratiques d'agriculture -- Canada; Étudiants en agriculture -- Canada; Enseignement agricole -- Canada; Écoles d'agriculture -- Canada; Agriculture -- Recherche sur le terrain -- Canada; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; NATURE -- Natural Resources; Agricultural colleges; Agricultural education; Agricultural students; School farms; Canada; United States